2013
DOI: 10.3892/etm.2013.1068
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary hormone level changes and hypxonatremia in aneurysmal subarachnoid hemorrhage

Abstract: The aim of this study was to investigate the changes in serum pituitary hormone levels and the mechanism of hyponatremia in aneurysmal subarachnoid hemorrhage (SAH). Nuclear medical tests and serum electrolyte monitoring were performed in 49 aneurysmal SAH cases and 10 healthy volunteers. The levels of serum pituitary hormones were significantly higher in the SAH patients compared with the control group on days 1–3 and 7–9 after SAH onset (P<0.05). The peak value occurred on days 7–9. The rate of hyponatremia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…These patients had a greater tendency for hormonal changes, and perhaps more significant damage to the hypothalamus-pituitary occurred, consequent to ischemia and increased intracranial pressure. 5 Our study found 52.4% of patients with changes in cortisol; the majority observed only after the test stimulation of insulin, when there was the expected increase in subsequent doses of 7μg/dl. A subarachnoid hemorrhage by rupture of cerebral aneurysm is the cause of psychological stress, as well as the stress or pain due to increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 44%
“…These patients had a greater tendency for hormonal changes, and perhaps more significant damage to the hypothalamus-pituitary occurred, consequent to ischemia and increased intracranial pressure. 5 Our study found 52.4% of patients with changes in cortisol; the majority observed only after the test stimulation of insulin, when there was the expected increase in subsequent doses of 7μg/dl. A subarachnoid hemorrhage by rupture of cerebral aneurysm is the cause of psychological stress, as well as the stress or pain due to increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 44%
“…Trident pattern in pons area and peripheral fiber sparing is differential diagnosis with vasospasm, cerebral infarct and multiple sclerosis after non-aneurysmal perimesencephalic subarachnoid hemorrhage. 8) Aneurysm Y SIADH Saramma et al, 2013 16) Aneurysm Y CSW Hannon et al, 2012 5) Aneurysm Y SIADH Kubo et al, 2008 6) Aneurysm Y CSW Sherlock et al, 2006 17) Aneurysm Y SIADH Vrsajkov et al, 20121 9) Aneurysm Y CSW Nakagawa et al, 2010 12) Aneurysm Y CSW Wartenberg et al, 2006 20) Non-Aneurysm Y SIADH Chandy et al, 2006 3) Aneurysm Y CSW CSW: cerebral salt wasting; SIADH: Syndrome of inappropriate antidiuretic hormone secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Hyponatremia has also been reported to be associated with an increased risk of vasospasm. This may be the main reason for the poor prognosis of patients ( 18 ).…”
Section: Discussionmentioning
confidence: 99%